Perpustakaan Universitas Riau Dengan Pendekatan Arsitektur Perilaku - P, M Syukri Abdillah D; Aldy, Pedia; Amanati, Ratna (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Riau University library is a facility that managing and providing access to information services, resources, and knowledge that support teaching, learning, and research for the library users. The Existing of library building still not meet the functional requirements and user comfort. With presence of new library building planning in the University of Riau Masterplan year 2013-2033 became the reason for the design. Riau University library design is using the application of behavioral architecture approach with the intention that the designed libraries considering human aspects and behaviour. The concept that used in the design is behavioural accomodation. The design of Riau University Library is expected can meet the needs of user in terms of both function needs and users comfort by directing, and considering its behavior factor like privacy, territory, personal space.The results of the behaviour accomodation concept application contained in the design of Riau University library that includes zoning of function and behaviour, circulation that accomodate accessibility behaviour, indoor setting arrangement to accommodate behaviour and comfort, outdoor setting for outdoor actvity, form of mass wich is result from room setting, mass order inside the site, building structure, utilities that support function and comfort, building facades, vegetation and landscaping detail.Keywords: Behavioral Accomodation, Behavioural Architecture, Riau University Library